Analysis of Causes of Patient Safety by Nurses in the Installation Unit - Sukesi Niken; Ahmad Kholid; Wahyuningsih Wahyuningsih (GLOBAL HEALTH SCIENCE GROUP, 2021)
Patient safety in hospitals is a system where hospitals make patient care more comfortable. The system includes an assessment of effects, identification and management of related effects of sufferers, reporting and analysis of incidents, the ability to learn from incidents and their follow-up and implementation of solutions to minimize the occurrence of effects. The purpose of this study was to identify the factors that influence patient safety incidents. This research method is carried out with an analytical survey with a quantitative approach using a cross sectional design. The sample used was 30 respondents in July-August 2021. The results of this study were that there was a relationship between age, experience, competence, cooperation, communication, interference, and SOPs on patient safety incidents. There is no relationship between education and workplace comfort with patient safety. The conclusion is that nursing services based on patient safety must be carried out by nurses without being influenced by anything.